Interaction of decavanadate with interfaces and biological modelmembranesystems:Haracterization of soft oxometale systems - Aureliano, M. (2014)
Decavanadate is a polyoxometalate consisting of 10 octahedral vanadium centers, which has been found to exert biological effects and has been observed in vivo. Biological activity implies that a material is taken up into a cell or that the material interacts with membrane receptors. Because of the large size and the high molecular charge, it is nontrivial to anticipate how such a large anion interacts with membranes and whether it will be taken up by cells. Therefore, it becomes important to investigate how the anion interacts with membranes and membrane model systems. Since ion pairing is important for the interaction of this large complex with any membrane interface system, we investigate both the nature of Coulombic and neutral noncovalent interactions with membrane model interface systems and cellular systems. Specifically, we used microemulsions as model systems, and in the specific phase diagram regime where reverse micelles form. We find that, there is a large difference in the interaction with different interfaces, and that charge can have an important role. The negatively charged interface repels the anion, whereas a positive interface attracts the anion. However, the interface with neutral surfactant head groups also is found to repel the decavanadate. This result demonstrates that the discrete charge Coulombic interactions are not the only forces in effect, and that the interactions are at least to a first approximation dictated by the interface charge and not by the counterions in the system. Alternative forces include van der Waals attraction, pH of the water pool, and field and surface effects. Because biological membranes have differently charged ligands, it is not clear which interface systems provide the best analogy with cell surfaces. However, surface charge may affect the compounds and facilitate the interactions that could be important. For example, a positively charged surface could potentially facilitate hydrolysis and sequential abstraction of one or two vanadium atoms at a time from decavanadate. Recently, decavanadate was used as a structural model for the V2O5 material. Negatively charged interfaces have also been found to accelerate compound hydrolysis or in other ways alter reactions in compounds near the interface. Lipid-like interfaces potentially contribute to processing of coordination compounds. Decavanadate has been found to interact with proteins and insulin enhancing effects have been reported. Interactions with coordination compounds and the mechanisms of interactions should continue to be investigated because such systems may reveal the mode of interaction of these compounds.